How low can it go - corporate governance at Millennium Bcp - Lima, Rui Miguel Duarte (2020)
How low can it go is a case study, supported byteaching notes, which describesthe circumstances that ledto asignificant decrease on the stock price of Millennium BCP, the biggest Portuguese private bank. The case highlights the impactsofa failed succession plan on apublic institution, the consequentshareholder fight and the opacity which characterized the management of the bank.The governance modelrevisionsbrought no stability to the bank which leditsstock priceto a residual value. The initial separation between management and ownershipand the different shareholders’ interestsmade it very difficult for shareholders tolatercontrol and set astrategy for the bank.